2011
DOI: 10.1186/1471-2164-12-131
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of the Camellia sinensis transcriptome revealed candidate genes for major metabolic pathways of tea-specific compounds

Abstract: BackgroundTea is one of the most popular non-alcoholic beverages worldwide. However, the tea plant, Camellia sinensis, is difficult to culture in vitro, to transform, and has a large genome, rendering little genomic information available. Recent advances in large-scale RNA sequencing (RNA-seq) provide a fast, cost-effective, and reliable approach to generate large expression datasets for functional genomic analysis, which is especially suitable for non-model species with un-sequenced genomes.ResultsUsing high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
323
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(358 citation statements)
references
References 55 publications
28
323
4
3
Order By: Relevance
“…More than 61 % (67,373 of 109,486) unigenes were annotated by sequence similarity search in public databases. The percentages of the annotated unigenes were similar to those in Chinese fir (Huang et al 2012), parsley (Li et al 2014a, b) and tea (Shi et al 2011).…”
Section: Discussionsupporting
confidence: 49%
“…More than 61 % (67,373 of 109,486) unigenes were annotated by sequence similarity search in public databases. The percentages of the annotated unigenes were similar to those in Chinese fir (Huang et al 2012), parsley (Li et al 2014a, b) and tea (Shi et al 2011).…”
Section: Discussionsupporting
confidence: 49%
“…Altogether, BLAST searches against Nr, Nt, Swiss-Prot, GO, COG, and KEGG databases showed that a total of 21,605 (72.8% of 29,659) identified unigenes could be annotated with known biological functions. After Nr database annotation, the E-value distribution, identity distribution, and species distribution were then analyzed (Shi et al 2011) (Figure 1). For the E-value distribution of the predicted proteins, the top hits indicated that 41.2% of the mapped sequences had a significant similarity with a stringent threshold of less than 1e245, and 58.8% of the similar sequences ranged from 1e25 to 1e245 ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al (2005) sequenced 4,320 clones from a tea library and analyzed the sequences of a total of 2,963 ESTs. Recently, the transcriptome of tea was analyzed using a high-throughput Illumina RNAseq technique (Shi et al, 2011); however, no detailed functional characterization of gene products was attempted beyond preliminary biochemical assays (Singh et al, 2009;Zhang et al, 2012). Biochemical studies using leaf protein extracts revealed high activities of ANR in tea leaves and linked this to the formation of E and EGC ; the combined enzymatic reactions of dihydroflavonol 4-reductase (DFR) and LAR confirmed that the formation of catechin and GC proceeded from leucoanthocyanidins.…”
mentioning
confidence: 99%